Determinants of employee performance viewed from the aspect of management strategy: Motivation and work discipline - Mukrodi, Mukrodi; Sarwani, Sarwani (Privietlab, 2023)
This research aims to analyze the influence of motivation and discipline on employee performance at PT PLN. Quantitative research methods were used, with 85 respondents selected through sampling. Data was collected through questionnaires and analyzed using instrument tests, classical assumptions, multiple regression, coefficient of determination, and partial and simultaneous hypothesis testing with SPSS 26. The results show that motivation and discipline have a significant effect on the performance of PT.PLN employees. Simultaneously, both positively and significantly impact employee performance, with a coefficient of determination reaching 60.9%, while other factors influence 39.1%. The research concludes that motivation significantly increases employee productivity and performance at PT. PLN. Management can design motivation programs, such as financial incentives, career development, training, or work environment improvement. Discipline also has a positive effect, so it is necessary to develop policies that support and increase employee discipline levels through training and an effective reward and sanction system. Furthermore, the findings show that the combination of discipline and motivation positively impacts employee work results. Therefore, management needs to consider these two aspects to improve overall performance. Development programs that support discipline and motivation can be an effective strategy for achieving company performance goals.